Effects of surface concentration on the porphine monolayers: Molecular simulations at the nanoscale water-gas interface - Sriprajak Krongsuk (2018)
The effect of surface concentration on the structure and stability of porphine (PH 2 ) monolayers at the water-gas interface was studied by using molecular dynamics simulation. Five monolayer systems having different surface concentrations were investigated in order to cover a full range of the experimental π-A isotherm. The simulation results show that increment of a number of the PH 2 molecules not only affects the significantly decreasing water density at the interface but also the monolayer surface tensions. The calculated surface tensions of the five systems indicate that the monolayer phase transfer corresponding to gaseous, expanded, condensed, and collapsed phases are observed. The hydrogen bonding between water and the PH 2 molecules at the interface plays an important role on the monolayer film formation, especially at the lower surface concentrations. The PH 2 orientations for all surface concentrations, except the highest one, are favored to be the β-structure as observed in the copper porphyrazine (CuPz) monolayer. © 2011 Elsevier B.V. All rights reserved.